Effect of fermented soybean meal with probiotic and beta-glucan on some physiological and microbial traits of broiler chickens - karim, noora; Al-Asadi, Majid (University of Thi-Qar Journal of agricultural research, 2023)
The study aimed to investigate the effect of fermented soybean meal with probiotic and beta-glucan on some physiological and microbial traits of broiler chickens. The study was conducted from 12/2/2022 to 2/5/2022, at the animal field of the College of Agriculture, University of Basrah. This study included the manufacture of a device for fermenting soybean meal to raise its nutritional value by fermenting it, with probiotics or with beta-glucan. A total of 225 unsexed chicks, one day old, 40 gm broiler chickens Ross308 were used, they were prepared from one of the private hatcheries in Basra Governorate. The chicks were distributed randomly to five treatments, with three replicates (15 chicks per replicate), according to the Complete Random Design (CRD), the treatments were as follows; T0: Control treatment (basal diet), T1: added soybean meal with the addition of 0.5g/kg probiotics (without fermentation) to the basal diet. T2: added soybean meal with the addition of 0.5 g / kg+ 0.2% betaglucan (without fermentation) to the basal diet. T3: added fermented soybean meal with probiotic 0.5g/kg to the basal diet. T4: added fermented soybean meal 0.5g/kg+ 0.2% betaglucan to the basal diet. The results showed a significant increase in the percentage of total protein, albumin, globulin, and the number of lactobacillus bacteria, with a decrease in coliform bacteria of the fermented treatment and fortified with probiotic and beta-glucan compared to the control and non-fermented treatment.